Theoretical and numerical analysis of the corneal air puff test. (August 2016) - Simonini, Irene; Angelillo, Maurizio; Pandolfi, Anna
Abstract: Ocular analyzers are used in the current clinical practice to estimate, by means of a rapid air jet, the intraocular pressure and other eye's parameters. In this study, we model the biomechanical response of the human cornea to the dynamic test with two approaches. In the first approach, the corneal system undergoing the air puff test is regarded as a harmonic oscillator. In the second approach, we use patient-specific geometries and the finite element method to simulate the dynamic test on surgically treated corneas. In spite of the different levels of approximation, the qualitative response of the two models is very similar, and the most meaningful results of both models are not significantly affected by the inclusion of viscosity of the corneal material in the dynamic analysis. Finite element calculations reproduce the observed snap-through of the corneal shell, including two applanate configurations, and compare well with in vivo images provided by ocular analyzers, suggesting that the mechanical response of the cornea to the air puff test is actually driven only by the elasticity of the stromal tissue. These observations agree with the dynamic characteristics of the test, since the frequency of the air puff impulse is several orders of magnitude larger than the reciprocal of any reasonable relaxation time for the material, downplaying the role of viscosity during the fast snap-through phase.